Bionic artificial synaptic floating gate transistor based on MXene. (June 2022) - Cao, Y.X.; Zhao, C.; Liu, Z.J.; Chen, X.P.; Mitrovic, I.Z.; Liu, Y.N.; Yang, L.; van Zalinge, H.; Zhao, C.Z.
Highlights: A floating gate thin-film transistor based on MXene was fabricated. Several synaptic plasticities were successfully simulated. A high-pass filter application based on MXene floating gate transistor was proposed. Abstract: The ability to simulate biological neurobehavior with electronic devices has now attracted widespread attention. In the past few decades, people have tried a variety of device structures to simulate biological synaptic functions. Due to floating gate thin-film transistors' robust charge blocking and the existence of the tunneling layer, the trapped charge can be stored in a non-volatile manner, which has been considered one of the most suitable device structures for manufacturing artificial synapses. In this work, a photoelectric-stimulated artificial synaptic thin-film transistor was proposed. The MXene and self-assembled titanium dioxide on the surface serves as the floating gate layer and the tunneling layer, respectively. Moreover, the typical synaptic behaviors of synaptic transistors, such as excitatory postsynaptic current and paired-pulse facilitation, have been proven through electrical and optical pulse tests. Finally, through the simulation based on Butterworth's high-pass filter, the input images could be successfully sharpened. The characteristics of these photoelectric synapses reveal the huge potential of this device in neuromorphic vision applications. This work provides a very feasible solution for the application of artificial synaptic devices to image processing and recognition.